The Fatty Acid Content, Health Lipid Indices, and Instrumental, Histological, and Sensory Quality of Hare Meat (Lepus europaeus Pallas) - Gabriela Frunză; Marius-Mihai Ciobanu; Otilia Cristina Murariu; Răzvan-Mihail Radu-Rusu; Paul-Corneliu Boișteanu (Foods)
The aim of this work was to characterize the quality of meat from hares (Lepus europaeus Pallas), namely, the fatty acid content, health lipid indices, and instrumental, histological, and sensory profiles by gender and muscle type (Longissimus dorsi/LD vs. Semimembranosus/SM). The ΣPUFA/Σ SFA was higher for males, with an average value of 1.62/1. The Σn6/n3 ratio was elevated for males, with a mean value of 5.34/1. The mean meat essential fatty acids were 41.94%, the desirable fatty acids were 77%, and the polyunsaturation index was 6.09. Moreover, the atherogenic index was 0.72, the thrombogenic index was 0.71, the hypocholesterolemic/hypercholesterolemic (h/H) fatty acids ratio was 3.30, and the nutritive value index was 1.35. After the sensory analysis, the LD muscles showed higher scores in males for overall appreciation (4.20 vs. 3.95) but higher scores in females for SM muscles (4.14 vs. 4.00). Shear force was influenced by the ratio between muscle and connective tissue, and the proportion of collagen and protein was related to the number of muscle fibers. Muscle and connective tissues are inversely proportional, and their ratio is an indicator of the textural and mechanical properties of the analyzed samples. Hare meat is an appreciated resource for consumers in terms of its sensory, instrumental, and nutritional values, and it has a higher value than that obtained from livestock species or other wild animals (more valuable proteins, lower fat content, and better health lipid indices).